The Role of Surgical Treatment in Pulmonary Aspergilloma - Soysal, Omer; Kuzucu, Akin; Ozgel, Mehmet (Annals of Medical Research, 2021)
None
Keywords: Pulmonary Aspergilloma, Surgical Treatment, Tuberculosis, Hemoptysis